Antiparasitic effects of Zataria multiflora essential oil nano-emulsion on larval stages of Echinococcus granulosus - Karimi Yazdi, Monire (J Parasit Dis, 2020)
Various protoscolicidal agents are indicated for the prevention of recurrence of cystic echinococcosis caused by the larval stage of Echinococcus granulosus; however, most of these chemicals have adverse side effects. This study evaluated the effects of Zataria multiflora essential oil (ZEO) nano-emulsion and emulsion at the concentrations of 1, 2, 5, 10, 15, and 20 µl/ml on E. granulosus protoscoleces. Albendazole (5 mg/ml), normal saline, and nano-emulsion without ZEO served as control groups. Optimal concentrations of ZEO nano-emulsion and emulsion on the microcysts were also investigated. ZEO emulsion at a concentration of 20 µl/ml for the duration of 15 min and nano-emulsion for the duration of 10 min resulted in the death of 100% of the protoscoleces. Additionally, densely packed aggregates were formed inside the microcysts treated with ZEO nano-emulsion and emulsion at a concentration of 20 µl/ml after 40 min, but the complete destruction of laminated layers did not occur. The results indicate that ZEO nano-emulsions have a higher protoscolicidal effect than its emulsion, but these two compounds had similar effects on microcysts.